2020
DOI: 10.3390/genes11040401
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the CFTR Gene Discovery on Cystic Fibrosis Diagnosis, Counseling, and Preventive Therapy

Abstract: Discovery of the cystic fibrosis transmembrane conductance regulator (CFTR) gene was the long-awaited scientific advance that dramatically improved the diagnosis and treatment of cystic fibrosis (CF). The combination of a first-tier biomarker, immunoreactive trypsinogen (IRT), and, if high, DNA analysis for CF-causing variants, has enabled regions where CF is prevalent to screen neonates and achieve diagnoses within 1–2 weeks of birth when most patients are asymptomatic. In addition, IRT/DNA (CFTR) screening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 83 publications
0
26
0
2
Order By: Relevance
“…An exemplary collaboration involving more than 100 laboratories worldwide and carried out through an international consortium for the study of the gene mutations (Cystic Fibrosis Genetic Analysis Consortium) has led to the identification of more than 2000 different CFTR mutations to date [ 69 ]. The molecular exploration of this gene has enabled a better understanding of the genotype/phenotype correlations, improved the diagnosis and the management of CF patients and their families, and opened up the way to the emergence of mutation-specific therapies, which contribute to modify the epidemiology of CF [ 16 , 17 ]. In a very comprehensive article published in this special issue of Genes , Farrell et al reviews the “impact of the CFTR gene discovery on CF diagnosis, genetic counseling and preventive therapy” [ 16 ].…”
Section: The Impact Of the Discovery Of The Cftr mentioning
confidence: 99%
See 2 more Smart Citations
“…An exemplary collaboration involving more than 100 laboratories worldwide and carried out through an international consortium for the study of the gene mutations (Cystic Fibrosis Genetic Analysis Consortium) has led to the identification of more than 2000 different CFTR mutations to date [ 69 ]. The molecular exploration of this gene has enabled a better understanding of the genotype/phenotype correlations, improved the diagnosis and the management of CF patients and their families, and opened up the way to the emergence of mutation-specific therapies, which contribute to modify the epidemiology of CF [ 16 , 17 ]. In a very comprehensive article published in this special issue of Genes , Farrell et al reviews the “impact of the CFTR gene discovery on CF diagnosis, genetic counseling and preventive therapy” [ 16 ].…”
Section: The Impact Of the Discovery Of The Cftr mentioning
confidence: 99%
“…The discovery of the CFTR gene has also increased the performance of NBS for CF by introducing DNA analysis into the screening protocol, and thus improved the diagnosis and management of CF [ 16 , 78 , 79 ]. The coupling of the immunereactive trypsinogen assay to the search for CFTR mutations has eliminated the need for a second blood sample.…”
Section: The Impact Of the Discovery Of The Cftr mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CFTR-related disorders such as pancreatitis and bronchiectasis have been reported in carriers for over 20 years [ 9 ], and a recently reported, large study by Miller et al [ 10 ] has revealed that those with one CFTR variant have a significantly increased risk for 57 of 59 CF-related diagnostic conditions. Their observations and others reviewed elsewhere [ 11 ] challenge the concept of “healthy carriers,” which could become another refuted CF dogma. More fundamentally, as we have learned with sickle cell trait [ 11 ], the concept of recessive may be misleading.…”
Section: To the Editormentioning
confidence: 99%
“…Their observations and others reviewed elsewhere [ 11 ] challenge the concept of “healthy carriers,” which could become another refuted CF dogma. More fundamentally, as we have learned with sickle cell trait [ 11 ], the concept of recessive may be misleading. In fact, the new data suggest that the significance of having a single CFTR variant is more complex than we ever imagined.…”
Section: To the Editormentioning
confidence: 99%